A macrocyclic molecule with multiple antioxidative activities protects the lens from oxidative damage - Zhang, Jinmin; Yu, Yu; Mekhail, Magy A.; Wu, Hongli; Green, Kayla N. (Frontiers in Chemistry, 2022)
Growing evidence links oxidative stress to the development of a cataract and other diseases of the eye. Treatments for lens-derived diseases are still elusive outside of the standard surgical interventions, which still carry risks today. Therefore, a potential drug molecule OHPy2N2 was explored for the ability to target multiple components of oxidative stress in the lens to prevent cataract formation. Here we show that the OHPy2N2 molecule activates innate catalytic mechanisms in primary lens epithelial cells to prevent damage induced by oxidative stress. This protection was linked to the upregulation of Nuclear factor erythroid-2-related factor 2 and downstream antioxidant enzyme for glutathione-dependent glutaredoxins, based on Western Blot methods. The anti-ferroptotic potential was established by showing that OHPy2N2 increases levels of glutathione peroxidase and readily binds iron (II) and (III). The bioenergetics pathway, which has been shown to be negatively impacted in many diseases involving oxidative stress, was also enhanced as evidence by increased levels of ATP product when the lens epithelial cells were co-incubated with OHPy2N2. Lastly, OHPy2N2 was also found to prevent oxidative stress-induced lens opacity in an ex vivo organ culture model. Overall, these results link together the multiple pathways that the OHPy2N2 has the ability to impact to promote natural mechanisms within cells to protect against chronic oxidative stress in the eye.